The hippo pathway effector Yes‐associated protein promotes epithelial proliferation and remodeling in chronic rhinosinusitis with nasal polyps. Issue 4 (18th November 2018) - Deng, Huiyi; Sun, Yueqi; Wang, Weihao; Li, Meijiao; Yuan, Tian; Kong, Weifeng; Huang, Xuekun; Long, Zijie; Chen, Zhuanggui; Wang, Deyun; Yang, Qintai
Abstract: Background: Hippo‐Yes‐associated protein (YAP) pathway plays an important role in epithelial cell proliferation and development. However, its possible role in chronic rhinosinusitis with nasal polyps (CRSwNP) remains unknown. We aim to investigate it on nasal epithelial proliferation and remodeling in CRSwNP. Methods: The expressions of hippo pathway components as well as Ki‐67 and E‐cadherin in the sinonasal mucosa and nasal epithelial cells were analyzed in 14 controls, 14 eosinophilic CRSwNP, and 14 noneosinophilic CRSwNP. Nasal epithelial cells from 6 controls, 6 eosinophilic CRSwNP, and 6 noneosinophilic CRSwNP were cultured and treated with lipopolysaccharide (LPS), Poly(I:C), or a selective YAP inhibitor verteporfin (VP). Results: The hippo pathway components MST1, LATS1/2, YAP, and TEAD1 were increased in both eosinophilic and noneosinophilic CRSwNP, particularly in nasal epithelial cells, along with upregulation of Ki‐67 and downregulation of E‐cadherin. The mRNA levels of YAP positively correlated with the Ki‐67 mRNA levels, and negatively associated with the E‐cadherin mRNA levels in polyp tissues and epithelial cells from nasal polyps (NPECs). LPS and Poly(I:C) upregulated the YAP expression in nasal epithelial cells accompanied by increased TEAD1 and Ki‐67 expression. Conversely, YAP inhibition by VP decreased TEAD1 and Ki‐67 expression in NPECs. Conclusions: Hippo pathway components are abnormally upregulated in NPECs, and its effector YAP promotes nasal epithelial cells proliferation and remodeling in CRSwNP. It provides a rationale to explore inhibition of YAP as a novel therapeutic strategy for reducing the epithelial proliferation and remodeling in CRSwNP. Abstract : Hippo pathway is aberrantly expressed in nasal polyps. Hippo pathway effector Yes‐associated protein is involved in epithelial proliferation and remodeling in nasal polyps. Inhibition of Yes‐associated protein can reduce proliferation of nasal polyp epithelial cells.